Risk balance & security - Van Brunschot, Erin Gibbs (Sage Publications, 2008)
Van Brunschot and Kennedy capture the interdisciplinary realities facing public security today, and the means in which a risk balance is evident in the secruity decisions made to deal with crime, terrorist activities and environmental disasters.